2014
DOI: 10.1002/alr.21417
|View full text |Cite
|
Sign up to set email alerts
|

Cellular comparison of sinus mucosa vs polyp tissue from a single sinus cavity in chronic rhinosinusitis

Abstract: Polyps have a similar cellular composition to that of mucosa. Higher levels of ILC2s, plasma cells, pDCs, activated CD8 T cells, and IgG(+) B cells in polyp tissue may be reflective of cell populations driving nasal polyp development. The cellular machinery of CRS is present in polyps and representative of the disease process. This pilot study strongly suggests that a larger study would provide significant insights into the relationship of sinus mucosa to pathogenesis of nasal polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 50 publications
(25 reference statements)
0
23
0
3
Order By: Relevance
“…Although reports have shown reduced levels of the regulatory T cell (Treg) transcription factor Forkhead box P3 (FOXP3) and reduced FOXP3 + staining in polyp tissues, no change in Tregs was detected by flow cytometry in another study (133135). Treg activation in peripheral blood cells is reported to be reduced in CRS patients compared with control patients, but most studies do not find reduced levels of the suppressive cytokines IL-10 or TGF-β (136139).…”
Section: Innate and Adaptive Inflammatory Responses Underlying The Pamentioning
confidence: 89%
“…Although reports have shown reduced levels of the regulatory T cell (Treg) transcription factor Forkhead box P3 (FOXP3) and reduced FOXP3 + staining in polyp tissues, no change in Tregs was detected by flow cytometry in another study (133135). Treg activation in peripheral blood cells is reported to be reduced in CRS patients compared with control patients, but most studies do not find reduced levels of the suppressive cytokines IL-10 or TGF-β (136139).…”
Section: Innate and Adaptive Inflammatory Responses Underlying The Pamentioning
confidence: 89%
“…This study supports other studies that have found an increase in eosinophils and macrophages when comparing nasal polyp tissue to mucosa in CRSwNP patients. [40][41][42][43] This increase of inflammatory cells in polyps is thought to be a part of the disease process and accounts for the persistent inflammation seen in these patients. 1 Although these studies have reported mostly similar inflammatory cell dispersal between nasal polyps and mucosa, unlike our study they have also reported an increase in neutrophils, CD8 T cells, and plasma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Somit können durch IL-33-und IL-25-aktivierte ILC2 s eine eosinophile Atemwegsentzündung induzieren [71,72]. ILC2 s sind in nasalen Polypen reichlich vorhanden und stehen in Verbindung mit einer erhöhten Anzahl von Eosinophilen im Blut und Gewebe von Patienten mit NP und einer schwerwiegenden klinischen Symptomatik [73,74].…”
Section: Die Polyposis Nasi Als Immunologische Erkrankung Der Atemwegunclassified